Engineered Cobalt/Molybedum Bimetallic MOF as Electrochemical Signal Transducer for Uric Acid Detection - Shubhangi; Chaudhari R.; Rai S.K.; Chandra P. (My University, 2025)
Electrochemical signal transduction systems involving metal organic frameworks (MOFs) are new buzz words in sensing due to their astounding functional capabilities and catalytic potential. In this work, creation of one such novel sensing platform comprising of cobalt/molybdenum (Co/Mo) bimetallic MOF has been attempted for the sensitive detection of uric acid (UA) in clinical ranges. Conventionally, UA is detected through an enzyme called uricase which converts UA to allantoin. However, the enzyme-based diagnostic solutions are prone to chemical and thermal instabilities making the process cumbersome and tedious. To eliminate such challenges, the developed non-enzymatic detection system uses a highly catalytic bimetallic sensing module which electrochemically facilitates conversion of UA to allantoin, and yields electrochemical signal outcomes. The developed sensing probe was characterized through physical and electrochemical techniques such as scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and, cyclic voltammetry (CV). Here, UA has been used as the sample target analyte to validate the efficacy of the bimetallic system using differential pulse voltammetry (DPV) and chronoamperometry (CA). The preliminary results hold immense promise for the developed system in application for sensing a wide range of analytes through electrochemical methods in clinical settings. © 2024 IEEE.